2020
DOI: 10.1074/jbc.ra119.011527
|View full text |Cite
|
Sign up to set email alerts
|

The small molecule GAT1508 activates brain-specific GIRK1/2 channel heteromers and facilitates conditioned fear extinction in rodents

Abstract: G-protein–gated inwardly-rectifying K+ (GIRK) channels are targets of Gi/o-protein–signaling systems that inhibit cell excitability. GIRK channels exist as homotetramers (GIRK2 and GIRK4) or heterotetramers with nonfunctional homomeric subunits (GIRK1 and GIRK3). Although they have been implicated in multiple conditions, the lack of selective GIRK drugs that discriminate among the different GIRK channel subtypes has hampered investigations into their precise physiological relevance and therapeutic potential. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 78 publications
0
37
0
Order By: Relevance
“…Next, we probed the effect of PKC-mediated effects on the strength of channel–PIP 2 interaction by comparing the kinetics of inhibition due to dephosphorylation of PIP 2 before and after the channel was treated with PMA. The 5’-ptaseOCRL system has been used effectively to compare the influence of different channel modulators on the strength of channel–PIP 2 interactions ( 27 ). After the PMA-induced inhibition of TRPC5 currents reached a steady state ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we probed the effect of PKC-mediated effects on the strength of channel–PIP 2 interaction by comparing the kinetics of inhibition due to dephosphorylation of PIP 2 before and after the channel was treated with PMA. The 5’-ptaseOCRL system has been used effectively to compare the influence of different channel modulators on the strength of channel–PIP 2 interactions ( 27 ). After the PMA-induced inhibition of TRPC5 currents reached a steady state ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although F137 and D173 are required for ML297's ability to activate GIRK1-containing GIRK channels, it remains to be determined conclusively whether these amino acids interact directly with ML297. Computer modeling, mutagenesis, and medicinal chemistry studies have begun to shed more light on the role of these and other amino acid residues in activation of GIRK by ML297 and the closely structurally related compound, GAT1508 (93). These studies implicated additional residues as important for the preference for some compounds, like GAT1508 GIRK1/GIRK2 heteromers compared to GIRK1/GIRK4 heteromers.…”
Section: Ml297 Vu0810464 Gat1508 and Giga1: Selective Girk1-containing Girk Activatorsmentioning
confidence: 99%
“…The pore helix (F137) residue has been shown to be a critical Kir3.1 determinant for current potentiation of heteromeric Kir3 currents and also for ML297- and GAT1508-induced current potentiation ( 6 , 7 , 8 , 9 ). In addition, the M2 helix residue D173 was also shown to be critical for ML297- and GAT1508-induced current stimulation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that residues F137 and D179 in the Kir3.1 channel were critical for activation by ML297 and GAT1508. The double mutant Kir3.2:S148F/N184D + Kir3.2 WT could be activated by ML297 and GAT1508 ( 8 , 9 ), demonstrating that these two residues of Kir3.1 are necessary and sufficient for activation by these drugs. We tested the single Kir3.4:S143F, N179D and double Kir3.4:S143F/N179D mutants coexpressed with Kir3.4 and found that the Kir3.1 (F137) was necessary and sufficient for the selective inhibition of heteromeric GIRK channels by the BP-G1 compound ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation